2010
DOI: 10.3109/01942638.2010.541753
|View full text |Cite
|
Sign up to set email alerts
|

Relationships Between Fine-Motor, Visual-Motor, and Visual Perception Scores and Handwriting Legibility and Speed

Abstract: Occupational therapists assess fine motor, visual motor, visual perception, and visual skill development, but knowledge of the relationships between scores on sensorimotor performance measures and handwriting legibility and speed is limited. Ninety-nine students in grades three to six with learning and/or behavior problems completed the Upper-Limb Speed and Dexterity Subtest of the Bruininks-Oseretsky Test of Motor Proficiency, the Beery-Buktenica Developmental Test of Visual-Motor Integration-5th Edition, the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
54
0
2

Year Published

2013
2013
2023
2023

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 55 publications
(61 citation statements)
references
References 18 publications
3
54
0
2
Order By: Relevance
“…Additionally, our findings are congruent with results from a study that examined the relationship between sensorimotor skills, visual-motor integration, and handwriting in a diverse sample of children with learning or behavioral disabilities or both (Klein, Guiltner, Sollereder, & Cui, 2011). The researchers found that although sensorimotor skills explained little of the variance in handwriting proficiency, visual-motor integration was a significant predictor in classifying children as either "skilled" or "unskilled" handwriters.…”
Section: Discussionsupporting
confidence: 79%
“…Additionally, our findings are congruent with results from a study that examined the relationship between sensorimotor skills, visual-motor integration, and handwriting in a diverse sample of children with learning or behavioral disabilities or both (Klein, Guiltner, Sollereder, & Cui, 2011). The researchers found that although sensorimotor skills explained little of the variance in handwriting proficiency, visual-motor integration was a significant predictor in classifying children as either "skilled" or "unskilled" handwriters.…”
Section: Discussionsupporting
confidence: 79%
“…These tools have good reliability and validity. Some studies use visual perception and visual motor ability to predict English word recognition (Goyen & Duff, 2005;Kaiser, Albaret, & Doudin, 2009;Klein, Guiltner, Sollereder, & Cui, 2011). However, the characteristics of these visual perception tests vary greatly from those of Chinese language characters children read in Taiwan.…”
Section: A Tool To Assess Visual Perception In Taiwanmentioning
confidence: 98%
“…Examples are visual-motor integration, visual perception, fine motor function, kinaesthesia and biomechanical factors such as writing grasp, posture and muscle tone. Although the relationship of most of these performance components to handwriting speed and legibility has been examined (e.g., Feder & Majnemer, 2003;Goyen & Duff, 2005;Kaiser, Albaret & Doudin, 2009;Klein, Guiltner, Sollereder & Cui, 2011;Ryan, Rigby & Campbell, 2010;Schwellnus et al, 2012;Volman, van Schendel & Jongmans, 2006;Weintraub & Graham, 2000), substantial limitations exist in many of the studies. Participants in some studies did not have handwriting difficulties and some assessments used for identifying deficits in performance components had not been evaluated for psychometric rigour.…”
Section: Factors Assumed To Underlie Handwriting Difficultiesmentioning
confidence: 99%